2007
DOI: 10.1038/nsmb1278
|View full text |Cite
|
Sign up to set email alerts
|

CFTR regulatory region interacts with NBD1 predominantly via multiple transient helices

Abstract: The regulatory (R) region of the cystic fibrosis transmembrane conductance regulator (CFTR) is intrinsically disordered and must be phosphorylated at multiple sites for full CFTR channel activity, with no one specific phosphorylation site required. In addition, nucleotide binding and hydrolysis at the nucleotide-binding domains (NBDs) of CFTR are required for channel gating. We report NMR studies in the absence and presence of NBD1 that provide structural details for the isolated R region and its interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
334
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(370 citation statements)
references
References 52 publications
36
334
0
Order By: Relevance
“…Another likely possibility is that the deletion of the F508 residue affects the interaction of the R domain with other regions of CFTR. The R domain is thought to be largely disordered (Ostedgaard et al, 2000), but it contains ordered segments of helical structure (Baker et al, 2007), and it has been shown to interact directly with both the NBD1 domain (Baker et al, 2007), and with the N-terminal tail of CFTR (Naren et al, 1999). Translation of the R-domain is also important in ensuring that N-terminal regions of CFTR achieve a compact folded structure that can no longer be recognized by the Hsp40 Hdj-2 (Meacham et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another likely possibility is that the deletion of the F508 residue affects the interaction of the R domain with other regions of CFTR. The R domain is thought to be largely disordered (Ostedgaard et al, 2000), but it contains ordered segments of helical structure (Baker et al, 2007), and it has been shown to interact directly with both the NBD1 domain (Baker et al, 2007), and with the N-terminal tail of CFTR (Naren et al, 1999). Translation of the R-domain is also important in ensuring that N-terminal regions of CFTR achieve a compact folded structure that can no longer be recognized by the Hsp40 Hdj-2 (Meacham et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, we sought to pinpoint the first step at which the ⌬F508 mutation exerts its effect on CFTR folding, and we analyzed the stability of wild-type and mutant CFTR fragments by pulse chase ( Figure 5B). We first looked at the effect of deletion of F508 from a CFTR fragment consisting of amino acids 1-653, which stops at the NBD1 boundary before inclusion of the regulatory extension (Lewis et al, 2004;Baker et al, 2007). We found that CFTR 1-653 ⌬F508 accumulated to slightly lower levels than the wild-type fragment immediately after the labeling period (i.e., there was 27% less of 1-653 ⌬F508 in comparison with WT 1-653 at t ϭ 0).…”
Section: Mechanism Of ⌬F508-induced Misfolding Of Cftrmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that (1) split CFTR molecules could be cross-linked by introducing cysteines at the NBD dimer interface predicted from the crystal structures of other ABC transporters, and (2) PKA activation strongly enhanced cross-linking efficiency (confirmed by . Baker et al (2007) provided additional support for this type of mechanism in an NMR structural analysis of an R domain fragment. This fragment bound to recombinant NBD1 in solution with most of the contact points located at or near PKA sites.…”
Section: Mechanismmentioning
confidence: 99%
“…Our goal was to generate a set of models of CFTR in the closed channel state that is consistent with geometric constraints and our experimental data and that illustrates the dynamic nature of R region interactions with the NBDs. In particular, we focused on three elements of R region, for which chemical shift data show the highest fluctuating helical propensity (23) and broadening data show significant interactions with both NBD1 and NBD2 (Fig. 1).…”
Section: R Region Binds Multiple Partners In a Phosphorylation-dependentmentioning
confidence: 99%